Revolutionizing the driving experience: Mercedes-Benz cars and AI technology / Marlina Muhamad - Muhamad, Marlina (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Not everyone can afford an expensive car with AI technology, and many people may not have the opportunity to experience the benefits of AI-powered driving. However, it is essential to note that as technology advances, the cost of implementing AI in cars may decrease, making it more accessible to a wider range of people. Moreover, some car manufacturers are starting to incorporate AI technology in their more affordable models, further increasing its accessibility to people with lower budgets. Artificial Intelligence (AI) has been integrated into cars for several decades, with early applications focused on improving safety and performance. The use of AI in cars has been an ongoing process of innovation and refinement, with new applications and capabilities being developed over time to enhance safety, performance, and the overall driving experience. Prominent car brands like Tesla, Audi, BMW, Mercedes, and many luxury car manufacturers are incorporating AI technology in various ways to elevate the driving experience and improve safety. While owning a Mercedes car may be more affordable than luxury or sports cars from other high-end brands like Ferrari or Lamborghini, it is still considered a luxury vehicle and might come with a higher price point compared to mainstream car brands.